2020
DOI: 10.1186/s12284-020-00398-0
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development Strategies for Hybrid japonica Rice

Abstract: The utilization of heterosis has resulted in significant breakthroughs in rice breeding. However, the development of hybrid japonica has been slow in comparison with that of hybrid indica. The present review explores the history and current status of hybrid japonica breeding. With the creation of japonica cytoplasmic male sterility and photo-thermo-sensitive genic male sterile lines, both three-line and two-line systems of hybrid rice have been created, and a series of hybrid japonica rice varieties have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
(48 reference statements)
0
24
0
1
Order By: Relevance
“…The successful and efficient hybridization program dependent on the information of parental lines, the reproductive biology and development of rice, the conditions required to promote flowering and seed development, and the methods to synchronize flowering of various parents [23]. For sterile lines' traits by low stigma feature, the synchronization of flowering time with R lines is acute for seed production [3]. The flower synchronization between two parental lines of different GD can be achieved by seeding them on different dates, which are termed as seeding intervals [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful and efficient hybridization program dependent on the information of parental lines, the reproductive biology and development of rice, the conditions required to promote flowering and seed development, and the methods to synchronize flowering of various parents [23]. For sterile lines' traits by low stigma feature, the synchronization of flowering time with R lines is acute for seed production [3]. The flower synchronization between two parental lines of different GD can be achieved by seeding them on different dates, which are termed as seeding intervals [24].…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid varieties are generally developed by the three lines and the two lines breeding method. Meanwhile, in the three line method, the cytoplasmic genetic male sterility system is a three lines system that is involved and needed a cytoplasmic male sterile (CMS) source, a maintainer, and restorer (R) line is extensively being used in rice hybrids production [3]. Several factors influence the hybrid seed production, such as seeding time, field condition, planting pattern, weather conditions at flowering, synchronization of flowering in the parental lines, supplementary pollination techniques, and application GA3, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This limits the usage of japonica hybrid varieties. There is a fundamental need to exploit higher heterosis in japonica rice through enhancing available hybrid seed production systems [ 50 ]. To apply Hopum A to inter-subspecific hybrid rice breeding, a widely compatible Hopum with neutral hybrid sterility genes such as S24 and S5 [ 51 ] was used as a maintainer line for breeding widely compatible Hopum A.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, under the in uence of the genetic background of indica rice, hybrid japonica rice often exhibits premature senescence and differentiation between strong and weak ( lled and partially lled) grains. Additionally, during the later stages of growth, low temperature results in the incomplete lling of the weak grains, which prevents maturation, reducing the yield potential (Jin et al 2014;Zheng et al 2020). Previous research showed that the presence of too many indica components hindered its adaptation to the ecological conditions of northern China, and too few indica components restricted the expansion of the genetic distance between the parental lines, resulting in weak yield heterosis (Wang et al 2010;Lin et al 2012;Xie et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This limited development was mainly attributed to the fact that the heterosis in hybrid japonica rice was weaker compared with hybrid indica rice, which was due to the narrow genetic distance between the parental lines. Therefore, it was necessary to analyze the genetic background of the parental lines of hybrid japonica rice to select elite combinations, and it constituted an important technical strategy to improve its breeding e ciency (Pu et al 2015;Xie and Peng 2016;Yang et al 2016;Lin et al 2020;Zheng et al 2020). The genetic diversity and population structure of parental lines is an effective reference for breeding selection.…”
Section: Introductionmentioning
confidence: 99%